Multidimensional schizotypy and embodied emotions - Torregrossa, Lénie J.; Blain, Scott D.; Snodgress, Matthew A.; Park, Sohee (Frontiers in Psychology, 2023)
BACKGROUND: Disembodiment and socio-emotional deficits are core features of the schizophrenia spectrum from the prodromal stages to chronic illness. A recent study documented anomalous emotional embodiment in individuals with schizophrenia. Although bodily-self disturbances have been shown to precede and predict psychosis onset in at-risk populations, the etiology of anomalous emotional embodiment remains largely unexplored. The present study investigated bodily maps of emotions in relation to schizotypy to extend our understanding of embodied emotions in the schizophrenia spectrum. METHODS: 419 participants (312 female; 19.50 years ± 1.22) completed a topographical body mapping task where they reported patterns of embodiment experienced in the context of eleven different emotions and a neutral state (EmBODY, Nummenmaa et al., 2014). Embodied emotions were investigated in relation to multidimensional schizotypy. RESULTS: Individuals with elevated negative schizotypy experienced embodied emotions with higher intensity (r=.16, p=.003) but lower clarity (i.e., endorsing activation and deactivation in the same bodily location; β = -.28, 95% CI [-.54, -.03], Z=2.25, p=.02) and endorsed more incongruent bodily sensations of emotions (i.e., , reporting bodily activation in the context of a low-arousal emotion, r=.12, p=.05; reporting bodily deactivation in the context of high-arousal emotions, r=.13, p=.02 ). In line with the anomalous emotional embodiment documented in individuals with schizophrenia, some of these differences were particularly notable for low-arousal emotions. DISCUSSION: These results reveal negative schizotypy as a significant correlate of differences in emotional embodiment. More work is needed to link these differences to the anomalous bodily sensations of emotions documented in schizophrenia and assess their functional impact.